Reasons for Exoneration Among Fresh Evidence Cases in Canada - Weinsheimer, Camille C.; Giroux, Megan; Levy, Tamara; Connolly, Deborah A. (The Wrongful Conviction Law Review, 2025)
To help understand how to correct miscarriages of justice, we analyzed the exculpatory evidence that led to exoneration among Canadian cases of wrongful conviction. Fifty-nine fresh evidence cases were identified and data about each case was collected. We examined three main characteristics of the fresh evidence, including: 1) the availability of the evidence at the time of the original trial (i.e., whether the evidence was discovered after conviction, was not disclosed at the time of trial, or whether there was a new interpretation of the evidence after conviction); 2) the typical features of the evidence (i.e., the evidence type); and 3) who was responsible for initiating the reinvestigation based on this evidence (i.e., the catalyst who brought attention to the evidence that ultimately led to exoneration). We found that in 36% of cases, exculpatory evidence existed at the time of trial, but was not disclosed to defence counsel. In addition, we found that witnesses were the primary type of exculpatory evidence, suggesting witness interviewing may be a fruitful area for investigators to concentrate their efforts. We discuss policy implications in relation to these findings, and how investigators and legal teams might use this information to help guide their reinvestigations in order to more effectively and efficiently remedy wrongful convictions.